Pola konsumsi pangan, paritas, dan status gizi ibu pospartum 4 dan 6 bulan - IGA Putri Mahadewi; Hamam Hadi; Retna Siwi Padmawati (Jurnal Gizi Klinik Indonesia, 2008)
Background: Breastfed mothers are included in nutritional high-risk group. A the age of 4-6 months after postpartum, their weight start to decrease because of recovery and breastfeeding. Based on Susilo’s research, the prevalence of inadequate food intake of pregnant mothers in Bantul Regency is 28.69%. That high prevalence is caused by the lack of energy and protein intake. The nutritional status of breastfed mothers depend on their food intake during pregnancy. Nevertheless, the nutritional status of breastfed mothers aged 4 and 6 months who have sufficient and insufficient food intake are not known yet.Objective: To know the relationship between food intake pattern, the nutritional status during pregnancy, and parity with nutritional status of breastfed mothers aged 4 and 6 months.Method: This was observational research with cohort combined with concurrent and non-concurrent prospective study. Subjects were mothers who had baby aged 4 months. Data collected were mother’s nutritional status during pregnancy, nutritional status of breastfed mothers aged 4 and 6 months, food intake pattern (variety, quantity, frequency, avoidance of food), and economics social data (family, education, job, income, outcome, and parity). Food intake determined using FFQ. Data was analyzed descriptively and analytically with chi square and logistic examination. Multivariate logistic test was used to control variable that influence nutritional status of breastfed mothers.Results: The result showed that there was no relationship between food intake patterns during pregnancy with nutritional status of breastfed mothers aged 4 and 6 months. There was also no relationship between parity and nutritional status of breastfed mothers aged 4 and 6 months. Yet, there was significant influence between nutritional status during pregnancy with nutritional status of breastfed mothers aged 4 and 6 months (p<0.05). OR nutritional status during pregnancy and breastfeeding aged 4 month was 4.89:95% CI 1.63-14.7 and 6 month was 12:95% CI 2.37-15.81.Conclusion: The food intake pattern of breastfed mothers and parity did not influence nutritional status of breastfed mothers aged 4 and 6 months. However, the better the nutritional status of mothers during pregnancy, the better the nutritional status of breastfed mothers aged 4 and 6 months.